Landscape for children to play and learn: a conceptual comparison between natural stream and playground - Said, Ismail; Abu Bakar, Mohd. Sarofil (Penerbit UTM Press, 2005)
Playing And Moving Are The Central Of Young Children’s Lives. Allowing The Children To Experience The Natural And Man-Made Elements In Their Living Environment Would Generate Cognitive, Physical, And Social Skills Development. To Them Natural Forces Such As Rain And Wind, Natural Features Such As Vegetation, Animals And Landform, And Man-Made Elements Such As Buildings And Road Are Ubiquitous Elements In Their Living Environment. By Playing With Those Elements, They Learn To Perceive Their Benefits Or Adversities. Mobility And Perception In The Landscape Stimulate The Children’s Senses And Generate Feedbacks As Well As Affordances. Through Movement, The Children Perceive The Landscape Through Three Modes Of Learning Which Are Cognitive, Affective, And Evaluative. Two Contrasting Landscape Settings, A Stream And A Playground, Are Compared To Explain The Similarities And Differences Of Stimulations, Feedbacks, And Affordances, And The Modes Of Learning. The Landscape Is Described As An Ecological Dynamic Entity That Through Direct Experience Would Generate The Cognitive, Physical And Social Developments Of The Children. In Conclusion, It Is Important To Design And Develop Landscapes For Children That Stimulate Their Senses, Provide Feedbacks And Afford Functional Meanings To Their Cognitive, Physical And Social Skills.